Identification and characterisation of MS1 putative interacting proteins and regulatory targets in Arabidopsis - Yu, Suyang (2015)
The Arabidopsis thaliana MALE STERILITY1 (MS1) gene, encodes a plant homeodomain (PHD) transcription factor critical for viable pollen formation (Wilson et al., 2001). In the ms1 mutant, there are alterations in the production of pollen wall materials, as well as a failure of tapetal programmed cell death (PCD) (Vizcay-Barrena and Wilson, 2006). This ultimately results in the failure to produce viable pollen. Large numbers of genes are down-regulated in the ms1 mutant indicating that MS1 plays a key role in regulating late tapetal expression and pollen wall deposition (Ito et al., 2007; Yang et al., 2007).